IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA DI KABUPATEN KUANTAN SINGINGI (Studi Kasus Pantai Jai-Jai Raok) - Emilia Emharis; Rika Ramadhanti; Melliofatria Melliofatria (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
The tourism object favored by local tourists is Jai-Jai Raok Beach with its natural beauty of the countryside and beaches that are so eye-catching for visitors, moreover, the beauty of the beach can be seen from across the Batang Kuantan river and coincides with the location of Pacu Tepian Rajo, Pangean District. However, with the natural beauty, it is felt that the government still lacks attention, even though the government already has a policy on tourism development in Kuantan Singingi Regency. The government's lack of attention to the implementation of the policy, so researchers are interested in seeing the policy, whether it has been implemented or not regarding tourism in Kuantan Singingi Regency, especially the Jai-Jai Raok Beach Tourism Object, Padang Responsibility Village, Pangean District, Kuantan Singingi Regency. This can also be seen from several tourist attraction facilities that are inadequate and poorly maintained facilities, one example is the lack of landfills and the unavailability of changing room and toilet facilities. The theory used by the researcher is the theory of Public Policy Implementation, while the informants in this study are tourism object managers, visitors, and government parties using qualitative research types. Based on the results of field research obtained through informant information and also the results of the researcher's analysis it is known that the Implementation of Tourism Object Management Policy in Kuantan Singingi Regency (Case Study of Jai-Jai Raok Beach Tourism Objects) has been going quite well. This can be seen from several aspects, one of which is the increase in the number of visitors in the last few months and it is also apparent that several facilities have started to be built and community activities can also be held at Jai-Jai Raok Beach. Keywords; Policy Implementation, Tourism, Tiurism Development